Driving ESG Performance through Green Finance and Digital Transformation: The Strategic Role of CEO Foreign Experience - Tabah Rizki; Rafles Ginting; Windy Jatmika; Andi Amri (KEUNIS, 2026)
Globalization requires companies to integrate sustainability principles into their strategies to fulfil their environmental, social, and governance (ESG) commitments. This study examines green finance and digital transformation as complementary drivers of ESG performance in the ASEAN manufacturing sector, with CEO foreign experience as the moderating variable. Data were obtained from recent post-pandemic empirical evidence in emerging Southeast Asian markets from 2019 to 2023 and analyzed using the PLS technique. The results show that ESG performance is positively and significantly influenced by green finance and digital transformation, with CEO foreign experience strengthening these relationships. This study contributes theoretically by extending the ESG and strategic leadership literature through a leadership contingency perspective, highlighting how global exposure of the management enhances sustainability outcomes. The findings have a practical implication that ASEAN manufacturing companies should incorporate sustainable finance strategies, accelerate digital transformation, and prioritize globally experienced leadership to improve their long-term corporate sustainability performance.